2006
DOI: 10.1137/s0097539704445950
|View full text |Cite
|
Sign up to set email alerts
|

Word Problems and Membership Problems on Compressed Words

Abstract: Abstract. We consider a compressed form of the word problem for finitely presented monoids, where the input consists of two compressed representations of words over the generators of a monoid M, and we ask whether these two words represent the same monoid element of M. Words are compressed using straight-line programs, i.e., context-free grammars that generate exactly one word. For several classes of finitely presented monoids we obtain completeness results for complexity classes in the range from P to EXPSPAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
66
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 71 publications
1
66
0
Order By: Relevance
“…For instance, several polynomial time algorithms for the pattern matching problem on SLP-compressed input strings were developed [18,26,31,37]. In [28], the first author started to investigate the compressed word problem for a finitely generated group G with finite generating set Σ. For a given SLP G that generates a string over Σ and the inverses of Σ it is asked whether eval(G) represents the 1 of G (actually, in [28] the compressed word problem for finitely generated monoids was studied).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, several polynomial time algorithms for the pattern matching problem on SLP-compressed input strings were developed [18,26,31,37]. In [28], the first author started to investigate the compressed word problem for a finitely generated group G with finite generating set Σ. For a given SLP G that generates a string over Σ and the inverses of Σ it is asked whether eval(G) represents the 1 of G (actually, in [28] the compressed word problem for finitely generated monoids was studied).…”
Section: Introductionmentioning
confidence: 99%
“…In [28], the first author started to investigate the compressed word problem for a finitely generated group G with finite generating set Σ. For a given SLP G that generates a string over Σ and the inverses of Σ it is asked whether eval(G) represents the 1 of G (actually, in [28] the compressed word problem for finitely generated monoids was studied). This problem is equivalent to the well-known circuit evaluation problem, where we ask whether a circuit over a finitely generated group G (i.e., an acyclic directed graph with leafs labeled by generators of G and internal nodes labeled by the group multiplication) evaluates to the 1 of G. In [3], this problem was investigated for finite groups, and it was shown that there exist finite groups, for which the circuit evaluation problem is complete for P (deterministic polynomial time).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLPs turned out to be a very flexible compressed representation of strings, which are well suited for studying algorithms for compressed data, see e.g. [11,15,17,21,23,24]. In [18,26] it was shown that the word problem for the automorphism group Aut(G) of a group G can be reduced in polynomial time to the compressed word problem for G, where the input word is succinctly given by an SLP.…”
Section: Introductionmentioning
confidence: 99%
“…e.g., [13,8]. Our concern has been the evaluation of queries on XML documents that may be in a compressed form.…”
mentioning
confidence: 99%